Clinical confirmation of an infection with Echinococcus multilocularis (Mongolian genotype): first case report of human alveolar echinococcosis in Inner Mongolia, China - Xu Wang; Zhan-Jun Xiao; Chui-Zhao Xue; Wen-Ting Wu; Jiang-Hui Yang; Chun Yan; Ying Wang; Yan Kui; Wen-Bo Luo; Xi Du; Run-Na Zan; Rong-Jian Shang; et al. (Infectious Diseases of Poverty)
Abstract Background Alveolar echinococcosis (AE), caused by the larval stage of Echinococcus multilocularis, poses a substantial global health challenge due to its high mortality profile. This study reports the inaugural human infection of echinococcosis caused by the Mongolian genotype of E. multilocularis in China, also the first reported indigenous AE case in Inner Mongolia. Case presentation A 58-year-old female pastoralist from Inner Mongolia, who had no endemic region exposure history but prolonged occupational contact with dogs, presented with severe AE. Clinical examinations revealed a massive hepatic lesion exceeding 10 cm in diameter, accompanied by elevated eosinophils (0.90 × 109/L) and basophils (0.08 × 109/L). Despite undergoing liver transplantation, the patient succumbed postoperatively. Histopathological confirmation and molecular phylogenetics identified the Mongolian genotype of E. multilocularis infection, distinct from the predominant Asian genotype in China. Potential evidence of zoonotic transmission was discovered through genotype-matched E. multilocularis detection in corsac fox (Vulpes corsac) feces from the grasslands along the shores of Hulun Lake (Hulun Buir City, northeastern Inner Mongolia, China). Conclusions This report provides the primary evidence of a locally acquired human AE infection in China caused by the Mongolian genotype of Echinococcus multilocularis. The discovery of this case challenges historical classifications of echinococcosis endemic areas. The findings call for revised AE-endemic identification criteria, improved AE diagnostic protocols, and enhanced AE surveillance in the Inner Mongolia region to generate further epidemiological evidence and information on disease progression.